Arabic Lexicography Study in the Context of Applied Linguistics for Modern Arabic Language Learning - Firdaus, Ahmad Yanif; Ansori, Mohammad; Fahraini, Sovia (Al-Wasil, 2025)
Lexicography is a branch of applied linguistics that focuses on the compilation, analysis, and development of dictionaries or lexicons. In the context of Arabic language learning, lexicography has a strategic role as a bridge between linguistic theory and the practical needs of learners in understanding the meaning, use, and structure of Arabic vocabulary effectively. This study aims to explore the contribution of Arabic lexicography as part of applied linguistics in knowledge to support the development of Arabic language learning, especially for foreign speakers. This study uses library research with descriptive analysis used to examine various models of contemporary Arabic dictionaries and how they are applied in modern Arabic classes. The results of the study show that lexicography not only acts as a passive learning aid but can also be a medium for developing lexical and communicative competence. Such interactive electronic dictionaries provide great opportunities for facilitating learners with various learning styles. In addition, the development of corpus-based dictionaries has also been shown to increase the relevance of the context of vocabulary use according to actual needs. However, there are still challenges in integrating lexicography into the teaching curriculum, such as limited resources, lack of training for teachers, and the need for innovation in user-friendly dictionary design. Therefore, synergy is needed between lexicographers, teaching material developers, and education practitioners in designing applicable lexicographic instruments. This study concludes that Arabic lexicography is an important pillar in applied linguistics that has great potential to support functional and communicative Arabic language mastery.